2022
DOI: 10.1186/s13034-022-00490-x
|View full text |Cite
|
Sign up to set email alerts
|

School bullying victimization-associated anxiety in Chinese children and adolescents: the mediation of resilience

Abstract: Background School bullying victimization is associated with increased risk of anxiety in children and adolescents. However, little is known about the role of resilience in this association. The purpose of this study was to investigate the possible mediation by resilience in this association in a large group of Chinese children and adolescents. Methods A population-based cross-sectional study adopting two-stage simple random cluster sampling was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Scholars [73][74][75][76] argue that psychological resilience is a protective factor against school bullying, with a negative correlation between personal resilience and bullying incidents; higher personal resilience leads to reduced bullying risks. Research also con rms [29,40,44,69,77] that enhancing individual psychological resilience can buffer the impact of negative life events, aiding victims in overcoming crises, reducing the harm caused by bullying incidents, and lowering the risk of being bullied again. Simultaneously, individuals with higher levels of psychological resilience are less likely to bully others, indicating that increased personal resilience correlates with a reduction in school bullying incidents.…”
Section: Intermediary Role Of Psychological Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Scholars [73][74][75][76] argue that psychological resilience is a protective factor against school bullying, with a negative correlation between personal resilience and bullying incidents; higher personal resilience leads to reduced bullying risks. Research also con rms [29,40,44,69,77] that enhancing individual psychological resilience can buffer the impact of negative life events, aiding victims in overcoming crises, reducing the harm caused by bullying incidents, and lowering the risk of being bullied again. Simultaneously, individuals with higher levels of psychological resilience are less likely to bully others, indicating that increased personal resilience correlates with a reduction in school bullying incidents.…”
Section: Intermediary Role Of Psychological Resiliencementioning
confidence: 99%
“…Additionally, high psychological resilience often manifests as optimistic and positive emotional expression, proactive emotional and self-adjustment in the face of di culties or adversity, leading to sound decision-making and enhanced problem-solving abilities in interpersonal relationships, thereby helping to reduce the risk of school bullying [35][36][37][38][39]. Studies have con rmed [40][41][42][43][44] that there is a negative correlation between individual psychological resilience and school bullying, and as a protective factor against the risk of school bullying, psychological resilience should receive focused attention in research. It can be leveraged to alleviate the degree of bullying suffered by victims, thereby reducing the occurrence of school bullying.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience as a positive factor has been shown in many studies to mediate between many psychological factors. Several Chinese studies have shown that resilience has the mediated effect between childhood abuse and suicidal ideation in adolescents [32], resilience has the mediated effect between physical tness and anxiety in children [33], and resilience has the mediated effect between school bullying and anxiety in adolescents [34]. It has also been shown that resilience has the mediated effect between loneliness and depressive symptoms in elderly people in nursing homes [35].…”
Section: The Mediated Effect Of Resilience In Alexithymia and Nssimentioning
confidence: 99%
“…26 In addition, with the widespread use of mobile phones and the internet, a recent phenomenon known as cyberbullying victimization is also prevalent among adolescents. 18 , 27 It is worth noting that bullying victimization has major detrimental impacts on adolescents’ physical and mental health that are associated with a series of behavioral and emotional problems including depression, 28 anxiety, 29 loneliness, 30 low self-esteem, 31 even suicidal ideation, 32 etc. The affect-regulation model of NSSI states that NSSI is a maladaptive coping style to deal with adverse emotions caused by the experiences of victimization.…”
Section: Introductionmentioning
confidence: 99%